Pendampingan Strategi Pemasaran Kreatif untuk Menu Baru Ayam Gecok - Siswandi, Arif; Banyu Asmoro, Fachrial (VINICHO MEDIA PUBLISINDO, 2025)
Creative marketing strategy mentoring for the new menu, Ayam Gecok, aims to increase the visibility and appeal of the product in the increasingly competitive culinary market. Ayam Gecok, as a menu innovation that combines traditional flavors with modern presentation, requires an effective marketing approach to attract consumers' attention. In implementing this mentoring, various creative strategies were applied, including developing a strong brand identity, utilizing social media, and collaborating with culinary influencers. In addition, a market analysis was conducted to understand consumer preferences and current trends in the food industry. The results of this mentoring show an increase in brand awareness and consumer interest in Ayam Gecok, which is reflected in increased sales and positive interactions on digital platforms. Thus, the creative marketing strategy implemented not only succeeded in introducing this new menu, but also built a strong foundation for future product development. This activity is expected to be a model for other culinary business actors in developing and marketing new products effectively. Keywords: Ayam Gecok, Mentoring, Creative Marketing